2002
DOI: 10.4049/jimmunol.169.11.6376
|View full text |Cite
|
Sign up to set email alerts
|

Presence of HIV-1 Gag-Specific IFN-γ+IL-2+ and CD28+IL-2+ CD4 T Cell Responses Is Associated with Nonprogression in HIV-1 Infection

Abstract: HIV immunity is likely CD4 T cell dependent. HIV-specific CD4 T cell proliferative responses are reported to correlate inversely with virus load and directly with specific CD8 responses. However, the phenotype and cytokine profile of specific CD4 T cells that correlate with disease is unknown. We compared the number/function of Gag p24-specific CD4 T cells in 17 HIV-infected long-term nonprogressors (LTNPs) infected for a median of 14.6 years with those of 16 slow progressors (SPs), also HIV infected for a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
156
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(181 citation statements)
references
References 54 publications
18
156
1
6
Order By: Relevance
“…HIV-specific CD4 ϩ T Em cells from subjects with chronic HIV infection proliferate poorly and lack the ability to secrete IL-2 (2-4). The loss of these functions is correlated with HIV disease progression and is thought to contribute to the inability of the immune system to control infection (3,(5)(6)(7)(8). In recent years, significant effort has been devoted to the identification of biomarkers of HIV disease progression and T cell dysfunction.…”
Section: T Cell Dysfunction In Chronic Hiv Infection Is Closelymentioning
confidence: 99%
“…HIV-specific CD4 ϩ T Em cells from subjects with chronic HIV infection proliferate poorly and lack the ability to secrete IL-2 (2-4). The loss of these functions is correlated with HIV disease progression and is thought to contribute to the inability of the immune system to control infection (3,(5)(6)(7)(8). In recent years, significant effort has been devoted to the identification of biomarkers of HIV disease progression and T cell dysfunction.…”
Section: T Cell Dysfunction In Chronic Hiv Infection Is Closelymentioning
confidence: 99%
“…A correlation between the presence of antigen-specific CD4 T cells coproducing multiple cytokines and nonprogressive chronic HIV-1 infection has been shown in several cross-sectional studies. [9][10][11][12] Multifunctional CD4 or CD8 T cells are further proposed to represent a correlate of vaccinemediated protection against various infectious diseases. 6,[13][14][15] Although initial studies characterized the expression profile of IFN-g and interleukin (IL)-2, 9-11 more recent studies have expanded the investigation and analyzed more complex functional patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, cross-sectional studies suggest that high HIV-1 RNA loads are associated with loss of virus-specific CD4 + T cells with proliferative and IL-2-secreting capacity although virus-specific IFN-c-secreting CD4 + T cells are detectable throughout the course of HIV-1 infection [4, 8,16]. The presence of higher levels of CD4 + IL-2 + T cells in aviraemic subjects suggests that these cells have a role in HIV-1 control, but whether this is cause or effect is uncertain [17,18]. A recent prospective study showed that the presence of functional virus-specific CD4 + T cells in acute HIV-1 infection did not predict long-term control [19].…”
Section: Introductionmentioning
confidence: 99%